ANALISIS PENINGKATAN HUBUNGAN MESIR – ISRAEL PADA PERIODE PERTAMA MASA PEMERINTAHAN ABDEL FATTAH AL-SISI TAHUN 2014-2018 - Muhammad Khoirul Huda (UNIDA Gontor, 2018)
After experiencing the ups and downs, the relationship between Egypt and Israel significantly increased under the leadership of President Abdel Fattah al-Sisi who was sworn in on June 8, 2014. The main priority in this era is to tackle terrorism and improve regional safety and security, and rely on Israel as a strategic partner. This cooperation is mutually beneficial for both parties, Egypt is increasing its position in relations with the US and European Union, while Israel guarantees the continuation of Egypt’s favorable foreign policy. The restoration of Egyptian-Israeli relations is also part of a consolidation of the anti-Iran bloc which includes Israel, Saudi Arabia and Egypt.